Effect of target velocity on damage patterns in hypervelocity glancing collisions. (October 2020) - Dorogoy, A.; Rittel, D.; Weihs, D.
Highlights: Normal and glancing collisions result in highly different crater and damage patterns. The damage pattern is influenced by the projectile and target velocities ratio. At lower velocity ratios, the crater gets shallower and more elongated. Glancing collisions are not oblique colisions. Abstract: The collisions of space debris, whether human-origin or natural, and spacecraft are essentially hypervelocity impacts. Such collisions pose a serious threat to satellites and spacecraft. While multiple studies, both theoretical and experimental, have dealt with such collisions, none has thoroughly considered the effect of the target's motion during penetration. This results in a different type of collision, beyond normal or oblique penetration, referred to as glancing collision in this work. This paper studies numerically the effects of such glancing collisions, in which the speeds of both participants are of the same order of magnitude, and not collinear. As an example a simulation of a collision between a projectile moving at 2-10 km/s and a finite target plate moving at 10 km/s laterally, both made of 6061-T6 alloy, also compared to experimental data. The resulting damage is compared to that caused by normal, including comparison with existing experimental data, as well as oblique impact by projectiles at the same velocities where the target is stationary. Two types of projectiles were considered: a sphere and a short cylinder having a hemispherical head. The investigation reveals that glancing collisions result in vastly different craters' shapes and damage patterns with respect to normal collisions. The craters become shallower and more elongated and the damage is not axisymmetric. While the glancing collision is similar to oblique collision for spherical projectiles, it becomes vastly different for elongated non-spherical projectiles.